2019
DOI: 10.3892/ijmm.2019.4406
|View full text |Cite
|
Sign up to set email alerts
|

Carbenoxolone decreases monocrotaline‑induced pulmonary inflammation and pulmonary arteriolar remodeling in rats by decreasing the expression of connexins in T lymphocytes

Abstract: The adaptive immune response mediated by T lymphocytes is a well-established factor in the pathogenesis of pulmonary inflammation. changes in the expression of various connexins (cxs) or disruption of connexin-mediated cellular communication in T lymphocytes contribute to inflammation or tissue remodeling. The aim of the present study was to investigate the potential therapeutic value of blocking cxs in a monocrotaline (McT)-induced pulmonary inflammation rat model. Carbenoxolone (CBX) was used to inhibit conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The aforementioned studies all demonstrate that protection against PH is associated with preservation of connexin expression and/or localization. In contrast, monocrotalinetreated rats have an increased number of Cx40-and Cx43-expressing CD4 + and CD8 + T cells in lung tissue and the administration of the unspecific gap junction blocker carbenoxolone decreases the expression of these connexins and reduces RV hypertrophy in monocrotaline-treated rats [100]. These data show that the inhibition of connexins decrease the monocrotaline-induced pulmonary inflammatory response.…”
Section: Connexins and Treatment Of Pulmonary Hypertensionmentioning
confidence: 72%
“…The aforementioned studies all demonstrate that protection against PH is associated with preservation of connexin expression and/or localization. In contrast, monocrotalinetreated rats have an increased number of Cx40-and Cx43-expressing CD4 + and CD8 + T cells in lung tissue and the administration of the unspecific gap junction blocker carbenoxolone decreases the expression of these connexins and reduces RV hypertrophy in monocrotaline-treated rats [100]. These data show that the inhibition of connexins decrease the monocrotaline-induced pulmonary inflammatory response.…”
Section: Connexins and Treatment Of Pulmonary Hypertensionmentioning
confidence: 72%
“…p-p65 is the key target of the classic inflammation-related NF-κB signalling pathway, CD86 is a surface marker of M1polarized macrophages, and iNOS is a pro-inflammatory molecule associated with the inflammatory process. Our previous research on Cx43 showed that carbenoxolone decreased monocrotaline-induced pulmonary inflammation in rats by decreasing the expression of Cxs in T lymphocytes (Zhang et al, 2020). Angiotensin II induced RAW264.7 macrophage polarization toward the M1 phenotype through the Cx43/NF-κB pathway (Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Two professional pathologists randomly selected 20 different non-overlapping fields from each section and analyzed PVR and lung fibrosis with Image-Pro Plus v.6.0 software (Media Cybernetics, Inc.). The pulmonary fibrosis index was analyzed by calculating the ratio of the total area of collagen to the total area of connective tissue in each field of view, as previously described (32).…”
Section: Animal Model and Treatment Strategy A Total Of 12mentioning
confidence: 99%